Quality of care and satisfaction in mothers of children under 5 years of age who attend a primary health care facility in Lima - Perez-Siguas, Rosa (International Journal of Innovative Research and Scientific Studies, 2025)
To identify the relationship between quality of care and satisfaction in mothers of children under 5 years of age who attend the well-child check-up clinic at a primary health care facility in North Lima. The approach adopted was quantitative and the design was correlational-cross-sectional. The population consisted of 420 duly selected informant mothers, to whom the two measurement instruments were applied. There was a significant relationship between the construction of quality of care and satisfaction (p<0.05). Similarly, a significant relationship was found between the dimensions of quality of care (scientific and technical care, human care, and context of care) and satisfaction in all cases (p<0.05). According to the quality of care, the elevated level prevailed (55.7%), followed by medium (24.5%) and low (19.8%). According to satisfaction in mothers, the acceptable value prevailed (52.4%), followed by in process (24.5%) and to improve (23.1%). Finally, there is a relationship between quality of care and waiting time (p<0.05), as well as between satisfaction and waiting time (p<0.05). There was a meaningful relationship between the construction’s quality of care and satisfaction.